Macro/monetary relationships in the Caribbean : an eclectic review of literature - Farrell, Terrence W. (Institute of Social and Economic Research KingstonJM, 1986)
Reviews literature on macro/monetary relationships in the Caribbean from the early 1960's to 1986. Reviews works on the subject by authors such as C.Y. Thomas, A. McIntyre, T.W. Farrell, M. Howard and others.